The Influence of Fraud Diamond, Beneish M-Score and Dechow F-Score in Detecting Financial Statement Fraud in Agricultural Companies in the Plantation Sub-Sector (Listed on the IDX) - Andini Hajeriah Mualim; Linda Wahyu Marpaung; Stephen C. Fajardo; Safa D. Manala-O (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The focus of the study is to examine the Influence of Fraud Diamond, Beneish M-Score and Dechow F-Score in Detecting Financial Statement Fraud. This study was conducted to demonstrate that applying theoretical and quantitative fraud detection models can help identify the likelihood of financial statement manipulation. Companies that are evaluated using these approaches are expected to show more transparent and accountable financial reporting practices, thereby strengthening investor confidence and improving corporate governance. Secondary data serves as the data source for this study, which uses quantitative data types. A population of 32 in the Agricultural Companies in the Plantation Sub-Sector was taken from the Indonesia Stock Exchange website for the period 2021-2024 as many as 20 samples using the Purposive Sampling method. Hypothesis testing was conducted using logistic regression analysis using SPSS 26.0 software. The results showed that Fraud Diamond, Beneish M-Score, Dechow F-Score simultaneously influenced Financial Statement Fraud. ACHANGE, ROA, RECEIVABLE, BDOUT, AUDCHANGE partially influenced Financial Statement Fraud. While LEV, DCHANGE, Beneish M-Score, Dechow F-Score partially did not have a significant effect on Financial Statement Fraud.